Model Integrasi Pendidikan Karakter Berbantuan Media Prezi dalam Pembelajaran IPAS Bagi Siswa Kelas V SD - P.F, Bunga Adelia; Aisyah, Annisa Putri; Supriyadi, Supriyadi; Hermawan, Jody Setya (Universitas Pahlawan Tuanku Tambusai, 2024)
The decline in moral values among students today highlights the importance of integrating character education into the learning model. In the implementation of the Kurikulum Merdeka in elementary schools, IPAS (Science and Social Studies) lessons include the strengthening of character values. This educational focus is not only on academic knowledge but also on shaping students' character, such as a sense of responsibility, empathy towards others, and environmental awareness. The main goal is to educate students to become individuals who are not only academically intelligent but also possess good character and contribute positively to society. However, in reality, many students are still disinterested or feel bored with conventional teaching methods, often due to the monotonous and less interactive delivery of material. To address this issue, this research aims to introduce innovation in the learning process through the use of interactive media. Prezi was chosen as an alternative media option capable of providing a more dynamic, engaging, and interactive learning experience, with the hope of increasing students' interest and active participation in learning activities.